Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1442-2018.2011.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of midlife women's attitudes toward menopause in Turkey

Abstract: This study used a cross-sectional descriptive design to examine the attitudes of 154 Turkish women aged ≥ 40 years towards menopause. A questionnaire and the Menopause Attitudes scale were used. The mean score of the attitudes was determined as 34.70 ± 8.56. Most women in the study had negative attitudes towards menopause. The majority of women with positive attitudes were older, well educated and had used hormone replacement therapy (P < 0.05). Using multiple linear regression analysis, age and education leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
2
12
1
6
Order By: Relevance
“…In the present study, we found that a high percentage of women had neutral or positive attitude. In contrast, some studies reported that most women have negative attitude toward menopause [21,22]. This finding can be interpreted in light of the general life context of women and that menopause may simply be one transition in natural life's course.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that a high percentage of women had neutral or positive attitude. In contrast, some studies reported that most women have negative attitude toward menopause [21,22]. This finding can be interpreted in light of the general life context of women and that menopause may simply be one transition in natural life's course.…”
Section: Discussionmentioning
confidence: 99%
“…A partir dos 36 artigos selecionados constatou-se que 12 artigos se aproximaram por terem como intuito compreender os significados, conhecimentos, percepções e vivências atribuídas pelas mulheres sobre a menopausa e suas repercussões, principalmente para a sexualidade (Almeida, Luz, & Monteiro, 2007;Araújo et al, 2013;Coelho, Daher, Santana, & Santo, 2010;Costa, & Gualda, 2008;Feltrin, & Velho, 2014;Frugoli & Magalhães-Júnior, 2011;Hinchliff, & Gott, 2008;Kisa, Zeynelog, & Ozdemir, 2012;Trench & Rosa, 2008;Valadares et al, 2013;Wood, Mansfield, & Koch, 2007;Zampieri et al, 2009).…”
Section: Percepções Das Mulheres Idosas Sobre As Repercussões Da Menounclassified
“…Além disso, as mulheres destacaram a menopausa como uma experiência negativa e associada à diminuição do desejo e do prazer sexual, às mudanças estéticas, à perda da atração e da sensualidade e principalmente a modificação do papel social feminino (Araújo et al, 2013;Hinchliff, & Gott, 2008;Kisa et al, 2012;Trench, & Rosa, 2008;Zampieri et al, 2009). …”
Section: Percepções Das Mulheres Idosas Sobre As Repercussões Da Menounclassified
See 2 more Smart Citations